2012
DOI: 10.1007/s11250-012-0243-9
|View full text |Cite|
|
Sign up to set email alerts
|

Serological surveillance reveals widespread influenza A H7 and H9 subtypes among chicken flocks in Egypt

Abstract: Multiple avian influenza viruses' subtypes are circulating worldwide possessing serious threat to human populations and considered key contributors to the emergence of human influenza pandemics. This study aimed to identify the potential existence of H7 and H9 avian influenza infections circulating among chicken flocks in Egypt. Serum samples were collected from chicken flocks that experienced respiratory distresses and/or variable mortality rates. H7 and H9 virus infections were screened by haemagglutination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…These mutations have not been detected in any other H9N2 virus from Egypt so far, and due to the conservation of chemical properties, their effect on antigenicity is unclear. Also unique to Egyptian H9N2 viruses M2 V27I presumed to be associated with amantadine resistance was detected in three isolates; no further amantadine resistance markers were present (Belshe et al, 1988) Previously undescribed in the HA of Egyptian H5N1 viruses was an additional, sixth, PGS at (Afifi et al, 2013). BEAST analysis carried out here narrowed the possible introduction date of H9N2 viruses into Egypt to July-August 2009 (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…These mutations have not been detected in any other H9N2 virus from Egypt so far, and due to the conservation of chemical properties, their effect on antigenicity is unclear. Also unique to Egyptian H9N2 viruses M2 V27I presumed to be associated with amantadine resistance was detected in three isolates; no further amantadine resistance markers were present (Belshe et al, 1988) Previously undescribed in the HA of Egyptian H5N1 viruses was an additional, sixth, PGS at (Afifi et al, 2013). BEAST analysis carried out here narrowed the possible introduction date of H9N2 viruses into Egypt to July-August 2009 (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Also, serological investigation revealed that the H9N2 virus was wide-spread in commercial farm settings between February 2009 and April 2012. 68 About 50% (605/ 1225) of collected sera from 39 chicken flocks were tested positive for H9 subtype. 68 In another study, 165 commercial flocks and only 3 cases of backyards were found positive.…”
Section: H9n2mentioning
confidence: 99%
“…68 About 50% (605/ 1225) of collected sera from 39 chicken flocks were tested positive for H9 subtype. 68 In another study, 165 commercial flocks and only 3 cases of backyards were found positive. 16 In 2011-2013, one study identified H9N2 in 24 out 60 broiler, one out of 5 layer and one out of 5 breeder flocks 69 and the second study isolated the virus from 22 broiler flocks.…”
Section: H9n2mentioning
confidence: 99%
See 2 more Smart Citations